2021
DOI: 10.1021/acs.jpcc.1c00166
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Nanodiamonds to Onion-like Carbons by Ambient Electrospray Deposition

Abstract: Onion-like carbons (OLCs) are a class of fullerene-like circular nanoallotropes of carbon, typically synthesized from nanodiamond (ND) via thermal annealing, plasma spraying, and laser ablation. These methods require high temperature, high vacuum, or inert gas. Here, we report an ambient electrospray deposition (AESD) process to transform NDs (11 ± 1 nm in size) into OLCs (50 ± 13 nm in size) in water. Transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), Raman spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Since the initial discovery of CNOs, many attempts have been made to identify the reaction conditions that yield high-purity CNOs in large quantities. These attempts have employed numerous methods using various raw-carbon precursors to synthesize CNOs, including annealing, [191] arc discharge, [192] gas-liquid detonation, [193] electrochemical, [194] CVD, [195] ambient electrospray deposition, [196] and plasma-spray from NDs. [197,198] However, our thorough analysis of the literature revealed that amongst these methods, only a few techniques have occupied the main streams of current research due to their substantial potential in producing significant quantities of CNOs that might meet the stringent demands of commercial production.…”
Section: Synthesis and Fabrication Of Carbon Nanoonionsmentioning
confidence: 99%
“…Since the initial discovery of CNOs, many attempts have been made to identify the reaction conditions that yield high-purity CNOs in large quantities. These attempts have employed numerous methods using various raw-carbon precursors to synthesize CNOs, including annealing, [191] arc discharge, [192] gas-liquid detonation, [193] electrochemical, [194] CVD, [195] ambient electrospray deposition, [196] and plasma-spray from NDs. [197,198] However, our thorough analysis of the literature revealed that amongst these methods, only a few techniques have occupied the main streams of current research due to their substantial potential in producing significant quantities of CNOs that might meet the stringent demands of commercial production.…”
Section: Synthesis and Fabrication Of Carbon Nanoonionsmentioning
confidence: 99%
“…Microdroplets have emerged as a powerful medium for rapid synthesis of molecules and materials. Such methods are sustainable means of synthesis as they require minimum reagents and minimal or no activating agents such as acids, catalysts, etc., are used . Electrospray deposition (ESD) of microdroplets is a powerful way of creating nanostructures for diverse applications. , This paper explores the use of microdroplets to address one of humanity’s most important problems, namely clean water, using microdroplet-derived nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Electrospray deposition (ESD) of microdroplets under ambient conditions is emerging as a new synthetic method for a range of nanomaterials including nanoparticles (NPs), [9] nanobrushes, [10] nanowires, [11,12] nanoclusters, [13,14] nanoplatelets or nanopyramids, [15] nanosheets, [16,17] monodispersed nanoparticles, [18] and nanosized onion-like carbon (OLC). [19] The properties and structures of these nanomaterials are highly dependent on the choice of collecting surfaces which can be flat metal surfaces, [15] Indium Tin Oxide (ITO) plates, [18,19] water films, [17] MoS 2 nanosheets, [16] Te nanowires, [20] or TEM grids. [10] Metal nanostructures are of great interest owing to their catalytic properties.…”
Section: Introductionmentioning
confidence: 99%